2016
DOI: 10.3389/fmicb.2016.01862
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of CTX-M-15 among ESBL Producers from Environment and Fish Gut from the Shores of Lake Victoria in Mwanza, Tanzania

Abstract: Extended-Spectrum Beta-Lactamase (ESBL)-producing bacteria are a common cause of healthcare and community-associated infections worldwide. The distribution of such isolates in the environment and their presence in fish as a result of sewage contamination is not well-studied. Here we examined fish and environmental samples from Mwanza city for the presence of ESBL-producing bacteria. From 196 fish sampled from local markets, 26 (13.3%) contained lactose-fermenting ESBL-producing bacteria, while 39/73 (53.4%) en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 45 publications
7
77
3
Order By: Relevance
“…They all harboured bla CTX-M-15 located in the chromosome, at the same insertion sites with sequence type-ST-6359 indicating clonality. Recent studies involving isolates from animals and humans have shown the bla CTX-M-15 allele to be predominant in humans, fish, and animals, suggesting a circulation of this gene among different settings [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…They all harboured bla CTX-M-15 located in the chromosome, at the same insertion sites with sequence type-ST-6359 indicating clonality. Recent studies involving isolates from animals and humans have shown the bla CTX-M-15 allele to be predominant in humans, fish, and animals, suggesting a circulation of this gene among different settings [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from humans the environment as well as animals that are a food source serve as reservoirs for ESBLs and studies done on different continents have documented evidence, which in part explains the global presence and spread of ESBLs (1,2,12).…”
Section: Discussionmentioning
confidence: 99%
“…The reservoirs of ESBL-producing E. coli are warm-blooded animals including humans, which can transmit the bacteria to different environments, for example, aquatic environments, through fecal pollution (Jiang et al, 2012). Recently, studies have reported ESBL-producing E. coli in seafood such as shrimps, sardines, farmed fish, Nile tilapia (Oreochromis niloticus) as well as in frozen mackerel (Jiang et al, 2012;Moremi et al, 2016b;Nasreldin and Khaldoon, 2015;Dib et al, 2018). It has been documented that urban sewage, for example, from hospitals, is an important source of ESBL-producing enteric bacteria (Ojer-Usoz et al, 2013;Abgottspon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Tanzania, ESBL-producing E. coli have been isolated from different sources such as human specimens, foods, and aquatic environments (Moyo et al, 2010;Moremi et al, 2016b). Although ESBL-producing E. coli have been reported in humans in different regions of Tanzania (Moyo et al, 2010;Seni et al, 2016;Katakweba et al, 2018) and also in livestock and poultry (Katakweba et al, 2018), the importance of livestock and their meats as sources of ESBL-producing E. coli is unknown.…”
Section: Introductionmentioning
confidence: 99%